Analysis of Diesel Spray Droplets Behavior using Shadowgraph Technique Images - Abdul Adam, Abdullah; R., Mamat; Yatsufusa, Tomoaki (2014)
This study investigates the effects of injection pressure and ambient temperature on distribution of number density and diameter of fuel droplet in diesel fuel spray by using shadow-graph photography technique. The large number of fuel droplets was statistically analyzed by newly developed algorithm. The results show that the larger-size particles exist closer to the spray tip. Higher injection pressure promotes atomization and high ambient temperature has great effect on formation of small-size droplet at early time of injection period, especially at up and midstream of the spray.